Personnel Selection and Person-Organization, Job-Fit, Implication for Employees’ Performance in Nigeria (International Journal of Scientific Research and Management (IJSRM), 2017)
Person- organization-job-fit can be seen as the degree of congruence between a person and the organization, on the one hand, and between a person and his job, on the other. This in turn determines employee performance. Studies of personnel selection process generally agree that how personnel are selected into organization has a high degree of affinity with person-organization-job fit. The present study has extensively tried to establish the compatibility between a person and the organization basing on the extent to which a person and the organization share similar characteristics and/or meet such other needs. The study has also tried to establish a relationship between the process of selecting an employee and the organization-person fit. After extensive review of literature, the paper concludes that the selection/recruitment process to a large extent determines organization-person fit, on the one hand, and person-job fit, on the other.